Risk Identification and Decision-Making in Low-Rank Coal Handling: FMEA-AHP - Prabawa, Ananta; Wasesa, Meditya (Jurnal Bisnis dan Pemasaran Digital, 2024)
Purpose: This study addresses the challenges posed by the increasing proportion of lower-ranking coal through proactive risk management in the Coal Preparation Plant (CPP) area of the PT. XYZ. Previous failures in handling lower-ranking coal have led to production delays and have negatively impacted the coal handling process. The analysis focuses on identifying, assessing, and prioritizing risks, and formulating optimal solutions to minimize their impact. Method: The methodology incorporates FMEA for risk identification and ranking, and proposes the top three risks and alternative solutions. Then, it proceeds with The Analytic Hierarchy Process (AHP), guided by criteria from Value-Focused Thinking (VFT), to determine the most optimal solution. Results: The top three identified risks and their corresponding solutions are as follows: (1) sticky material adherence to the drawdown hopper and chute wall causing material flow blockage and overfill, addressed by installing a booster pump on the existing water suppression system. (2) The accumulation of fine coal in closed spaces causes equipment burning, mitigated through periodic clean-up using a new portable blower or water. (3) Burning coal, causing fires inside the tunnel, was resolved by installing a thermal camera monitoring system. Conclusions: The study concludes that the handling of lower-ranking coal within the CPP area presents several critical risks primarily associated with excessive airborne coal dust, sticky materials, and fine coal accumulation. Airborne dust reduces visibility, posing safety hazards and health risks, while also interfering with sensors and contaminating nearby equipment. Sticky materials adhering to chutes and conveyors cause blockages, overfills, belt drift, and trigger false sensor alerts, significantly reducing operational efficiency. Limitations: The scope of the research will be limited to the specific area of the Coal Processing Plant (CPP) in the company and will be based on the characteristics of the lower-ranking coal in the company. Contributions: This study provides valuable guidelines for CPP stakeholders to minimize disruptions and improve the overall effectiveness of coal-handling activities.